Total bilirubin in athletes, determination of reference range - K Witek; J Ścisłowska; D Turowski; K Lerczak; S Lewandowska-Pachecka; A Pokrywka (Termedia Publishing House, 2016)
The purpose of this study was to determine a typical reference range for the population of athletes. Results of blood tests of 339 athletes (82 women and 257 men, aged 18-37 years) were retrospectively analysed. The subjects were representatives of different sports disciplines. The measurements of total bilirubin (BIT), iron (Fe), alkaline phosphatase (ALP), alanine aminotransferase (ALT) and gamma-glutamyltransferase (GGT) were made using a Pentra 400 biochemical analyser (Horiba, France). Red blood cell count (RBC), reticulocyte count and haemoglobin concentration measurements were made using an Advia 120 haematology analyser (Siemens, Germany). In groups of women and men the percentage of elevated results were similar at 18%. Most results of total bilirubin in both sexes were in the range 7-14 μmol ∙ L-1 (49% of women and 42% of men). The highest results of elevated levels of BIT were in the range 21-28 μmol ∙ L-1 (12% of women and 11% of men). There was a significant correlation between serum iron and BIT concentration in female and male athletes whose serum total bilirubin concentration does not exceed the upper limit of the reference range. Elevated concentrations of total bilirubin appear to be due to changes caused by regular exercise. The obtained upper limit of the reference range for total bilirubin concentration in the group of athletes is 29.0 μmol ∙ L-1. It seems reasonable to use dedicated reference values for total bilirubin concentration in relation to the group of athletes.